Hybrid LWFA–PWFA staging as a beam energy and brightness transformer: conceptual design and simulations. (12th August 2019) - Martinez de la Ossa, A.; Assmann, R. W.; Bussmann, M.; Corde, S.; Couperus Cabadağ, J. P.; Debus, A.; Döpp, A.; Ferran Pousa, A.; Gilljohann, M. F.; Heinemann, T.; Hidding, B.; Irman, A.; et al.
Abstract : We present a conceptual design for a hybrid laser-driven plasma wakefield accelerator (LWFA) to beam-driven plasma wakefield accelerator (PWFA). In this set-up, the output beams from an LWFA stage are used as input beams of a new PWFA stage. In the PWFA stage, a new witness beam of largely increased quality can be produced and accelerated to higher energies. The feasibility and the potential of this concept is shown through exemplary particle-in-cell simulations. In addition, preliminary simulation results for a proof-of-concept experiment in Helmholtz-Zentrum Dresden-Rossendorf (Germany) are shown. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.